Pengaruh Penyaluran Zakat Produktif pada Program Bandung Makmur terhadap Kesejahteraan Mustahik di Baznas Kota Bandung - Muhammad Gandhi Darmawan; Zaini Abdul Malik; Popon Srisusilawati (Bandung Conference Series: Sharia Economic Law, 2022)
Welfare is defined as a system of life and social life both material and spiritual which is filled with a sense of safety, decency, and inner and outer peace, Zakat is one of the most effective Islamic economic systems to improve welfare if managed properly To analyze the effect of productive zakat funds on the level of the welfare of mustahik in BAZNAS Bandung City, the aim is to determine the effect of productive zakat distribution in the prosperous bandung program on the welfare of mustahik in BAZNAS Bandung City. The research method used is a quantitative method. The type of data that will be used in this research is field research. The research begins by collecting quantitative data in the form of numbers and then systematically arranged and processed by the SPSS Statistics program. simple linear regression is used. Based on the results of research and data analysis that has been carried out, it can be seen that in this study explains that there is a positive and significant influence between the variables of productive zakat distribution in the prosperous bandung program on the welfare of mustahik in the Bandung City Baznas. It is known from the responses of respondents who stated that they agreed that information related to the amount of productive zakat assistance received could meet business needs) shows that the results of productive Zakat affect the welfare of mustahik.